Strategi Penyelenggaraan Program Sekolah Ramah Anak: Analisis Peran Kepala Sekolah di SD Tanjung Jabung Timur Jambi - Syamsul Huda; Dian Nisa Istofa; Farida (JMiE (Journal of Management in Education), 2021)
This research aims to describe the strategy of the principal in organizing a child-friendly school program at SDN 9/X Sido Mukti. This research uses descriptive qualitative methods. Data collection is done through observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions, and verification. The results showed that the implementation of child-friendly school programs began with child-friendly school program planning activities in accordance with SOPs and predetermined policies. The preparation of strategies to meet 6 indicators includes child-friendly school policies, the implementation of learning processes, facilities and infrastructure, trained educators and education personnel children's rights, child participation as well as parents and communities.